Japanische Impressionen in finnischer Poesie. Haiku- Gedichte von Risto Rasa - Szmytkowska, Anna (Folia Scandinavica Posnaniensia, 2010)
German advocate and writer of haiku Wolfgang Weyrauch has stated: “My poem is my knife”. The definition conveys the essence of haiku: maximal amount of content in only three lines. The traditional Japanese haiku consisted of 17 syllables. For the modern European haiku, the number of syllables is secondary. What remains invariable is the lack of rhyme and title, close relationship between the lyrical subject and nature, and reflection. City and mass media are new themes in modern haiku. From the country of anime and manga, haiku have spread to almost every corner of Europe, including the country of the Moomins and mobile phones. In February 2010, Finnish philology students of the Adam Mickiewicz University had the opportunity to meet Risto Rasa, one of the present-day writers of haiku in Finland. In Rasa’s poetry, you can find admiration of nature and the unusualness of seemingly usual every day phenomena. Rasa’s production is infiltrated by the Zen philosophy already present in the works of the 17th century Japanese haiku writers, such as Matsuo Basho. Rasa’s verses appear in three lines. They don’t have rhymes, yet maintain inner harmony.